ANALISIS PENGARUH PERENCANAAN PAJAK, FREE CASH FLOW, DAN KECAKAPAN MANAJERIAL PADA MANAJEMEN LABA - Purnami Putri, Ni Luh Made Dian; Wirakusuma, Made Gede (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.11.NO.12.TAHUN.2022, 2022)
Earnings management is the act of intervening in the preparation of financial statements so that it affects earnings which aims to achieve the interests of the company. Earnings management can be done by increasing, leveling, or decreasing company profits. This study aims to determine the effect of tax planning, free cash flow, and managerial skills on earnings management. The population of this study consists of 63 mining companies listed on the Indonesia Stock Exchange for the period 2018-2020. Sampling using purposive sampling method, where there are 17 companies that meet the sampling criteria. The analytical technique used is multiple linear analysis. The results of data analysis show that planning variables and free cash flow have an effect on earnings management. Meanwhile, the managerial skill variable shows that the results have no effect on earnings management.